Rare GBA1 genotype associated with severe bone disease in Gaucher disease type 1 - Paskulin, Lívia D'Avila (2021)
Introduction:Gaucher disease (GD) type 1 is a lysosomal disease characterised by hepatosplenomegaly, anemia,thrombocytopenia, bone changes, and bone marrow infiltration. The disease is caused by biallelic pathogenicvariants inGBA1which codes for glucocerebrosidase, an enzyme involved in the catabolic pathway of complexlipids.Aims:To report on the case of two sisters with GD type 1 who bear a genotype never reported in the literature.Case report:Patient 1 is a 47-year-old female diagnosed at 42 years of age with chronic lumbar pain, mildsplenomegaly, slightly reduced platelets and normal hemoglobin values, severe Bone Marrow Burden (BMB)score, high chitotriosidase activity, and low glucocerebrosidase. Patient 2 is a 50-year-old female, sister of pa-tient 1, who was diagnosed after familial screening. At 45 years of age, she had osteonecrosis of the left femurand a total hysterectomy because of uncontrollable bleeding. Atfirst evaluation, she had bone pain with a highBMB score, mild splenomegaly, normal hemoglobin, normal platelets count, elevated chitotriosidase activity,and low glucocerebrosidase activity. Both patients were found to be compound heterozygotes for thep.Glu388Lys and the p.Ser405Asn variants inGBA1.Conclusions:This is thefirst family with GD and this combination of variants which causes a phenotype re-markable for severe bone disease with no or mild hematological manifestations.